2011
DOI: 10.2217/pgs.11.93
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Analyses of Cisplatin-induced Nephrotoxicity Indicate a Renoprotective Effect of ERCC1 Polymorphisms

Abstract: Genetic polymorphisms in ERCC1 may be valuable predictors of cisplatin-induced nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…It is a kind of abitrary because the creatinine clearance after CDDP injection is also tightly related to the baseline value of creatinine clearance, which was not adjusted in this study. According to other studies (Tzvetkov et al 2011; Sprowl et al 2012), we chose the change ratio of eGFR as the indicator of renal function. To determinate the boundary of nephrotoxicity, we abitrarily employed the change of eGFR to baseline lower than −30 %, which seldom happened in patients with CBP-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is a kind of abitrary because the creatinine clearance after CDDP injection is also tightly related to the baseline value of creatinine clearance, which was not adjusted in this study. According to other studies (Tzvetkov et al 2011; Sprowl et al 2012), we chose the change ratio of eGFR as the indicator of renal function. To determinate the boundary of nephrotoxicity, we abitrarily employed the change of eGFR to baseline lower than −30 %, which seldom happened in patients with CBP-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was found that the same nonsynonymous single-nucleotide polymorphism in the OCT2 gene was associated with reduced cisplatin-induced nephrotoxicity in patients [173]. On the contrary, screening the DNA of 79 cancer patients receiving cisplatin-containing chemotherapy showed that polymorphisms in hOCT2 genes were not associated with cisplatin-induced nephrotoxicity [178]. Studying a total of 53 patients with advanced carcinomas, it was demonstrated that cancer patients carrying the OCT2 (A270S) genotype were less susceptible to cisplatin-induced nephrotoxicity, but not to hematological toxicity [179].…”
Section: Cellular Transport Of Cisplatinmentioning
confidence: 99%
“…However the results have been inconclusive, which might explain why we only got two hits in our literature-based approach. DNA-repair genes have previously been shown to play a role in the pharmacogenetics of platinum-based effects (28,29,32). One of our hits in the literature-based approach was a genetic variant in ERCC5, a DNA-repair gene, but this variant the genotyping failed in the validation cohort and it has a low minor allele frequency.…”
Section: Discussionmentioning
confidence: 99%